The Coming of age of the profession issues and emerging ideas for the teaching of foreign languages - Harper, Jane 1942-; Lively, Madeleine; Williams, Mary K. (Mary Karen) 1948- (Heinle & Heinle, 1997)
A collection of articles written by innovators in language pedagogy, this text is supported by a CD-ROM containingdemonstrations of Heinle technology products, transparency masters to accompany each of the articles, professional documents (ACTFL guidelines, National Standards), sample activities, examples of student work, and ideas forevaluation forms. Materials are organized into four sections: Teacher-Learner Roles, Presentation, Activities, and Evaluation. the end of each section there are suggested activities for reflection, selfassessment, and application of the ideas presented.